Ion-Acoustic Shock Waves in Nonextensive Electron-Positron-Ion Plasma. (14th January 2015) - Ferdousi, M.; Yasmin, S.; Ashraf, S.; Mamun, A. A.
Abstract: A rigorous theoretical investigation is made of ion-acoustic shock structures in an unmagnetized three-component plasma whose constituents are nonextensive electrons, nonextensive positrons, and inertial ions. The Burgers equation is derived by employing the reductive perturbation method. The effects of electron and positron nonextensivity and ion kinematic viscosity on the properties of these ion-acoustic shock waves are briefly discussed. It is found that shock waves with positive and negative potentials are obtained to depend on the plasma parameters. The entailment of our results may be useful to understand some astrophysical and cosmological scenarios including stellar polytropes, hadronic matter and quark-gluon plasma, protoneutron stars, dark-matter halos, etc., where effects of nonextensivity can play significant roles.